Resposta :
[tex]\left[\begin{array}{ccc}1&2\\3&1\end{array}\right] .x +\left[\begin{array}{ccc}0&3\\7&-1\end{array}\right] = \left[\begin{array}{ccc}8&10\\12&5\end{array}\right] \\\\\\\\\left[\begin{array}{ccc}1x&2x\\3x&1x\end{array}\right] + \left[\begin{array}{ccc}0&3\\7&-1\end{array}\right] = \left[\begin{array}{ccc}8&10\\12&5\end{array}\right] \\\\\\\\\\\left[\begin{array}{ccc}1x+0&2x+3\\3x+7&1x-1\end{array}\right] =\left[\begin{array}{ccc}8&10\\12&5\end{array}\right] \\\\[/tex]
1x + 0 = 8
1x = 8
x = 8/1
x= 8
2x + 3 = 10
2x = 10-3
2x = 7
x = 7/2
x= 3,5
3x + 7 = 12
3x = 12 -7
3x = 5
x = 5/3
x = 1,667
1x-1 = 5
x = 5 + 1
x = 6
Substituindo na matriz
[tex]\left[\begin{array}{ccc}1x+0&2x+3\\3x+7&1x-1\end{array}\right] = \left[\begin{array}{ccc}8&10\\12&5\end{array}\right] \\\\\\\\\left[\begin{array}{ccc}1.8+0&2.3,5+3\\3.1,667+7&1.6-1\end{array}\right] = \left[\begin{array}{ccc}8&10\\12&5\end{array}\right] \\\\\\\left[\begin{array}{ccc}8+0&7+3\\5+7&6-1\end{array}\right] =\left[\begin{array}{ccc}8&10\\12&5\end{array}\right] \\\\\\\left[\begin{array}{ccc}8&10\\12&5\end{array}\right] =\left[\begin{array}{ccc}8&10\\12&5\end{array}\right][/tex]